Immunolocalization and effect of low concentrations of Insulin like growth factor-1 (IGF-1) in the canine ovary - Cardilli, Diogo J.; Sousa-Oliveira, Kellen; Franchi-Joao, Carolina; Azevedo-Voorwald, Faviana [UNESP]; Machado-Silva, Marco A.; Oliveira, Joao Ademir [UNESP]; Sanchez-Calabuig, Maria Jesus; Toniollo, Gilson H. [UNESP]; Perez-Gutierrez, Jose F. (Wiley-Blackwell, 2020)
Insulin like growth factor-1 (IGF-1) plays an important role in the regulation of ovarian function. Despite its extensive study in several species, there is a paucity of information about IGF-1`s function and localization in the canine ovary. The aim of the present study was to assess the effect of IGF-1 on oocyte nuclear maturation and to immunolocalize the IGF-1 and its receptor (IGF-1R) in the ovary. Cumulus-oocyte complexes (COCs) were obtained from 34 bitches. The COCs from each bitch were incubated in TCM 199-HEPES in the absence (n = 199) or presence (n = 204) of 100 ng/ml IGF-1 for 96 hr at 38oC in 5% CO2, stained and evaluated for nuclear maturation by fluorescence microscopy. The results showed that the addition of IGF-1 did not have an effect (p > 0.05) on the nuclear maturation under these conditions. The immunohistochemical study revealed nuclear and cytoplasmic staining for IGF-1 and IGF-1R, respectively. Both were localized in all ovarian structures including the corpus luteum, but not in the granulosa cells from primordial follicles. In addition, IGF-1 was not localized in the oocytes in tertiary follicles. The results obtained show the presence of IGF-1 through the stages of follicular growth and in the corpus luteum of the canine ovary. However, its role on oocyte nuclear maturation could not be demonstrated.
Keywords: bitch; insulin like growth factor-1; maturation; oocyte